Anthropomorphic Assessment Of Philtrum (Cuestiones de Fisioterapia, 2025)
Six hundred normal individuals (females) of different age groups from Lucknow (India), belonging to Rajput(R)& Brahmin (B) community were included in this study. Various dimensions of philtrum, lips and mouth weremeasured. The results were compared with the available data for Nepalese, Malays and Indonesian Adults. Inthe population under study the philtrum, lips and mouth measurements differ in all dimensions with all thecompared populations and show no resemblance to the any. The analysis of the data does not simply indicatethe differences in the measurements throughout the world, but also points out changes which may have aforensic and clinical significance